Biochar-Facilitated Soil Remediation: Mechanisms and Efficacy Variations - Guo, Mingxin; Song, Weiping; Tian, Jing (Frontiers in Environmental Science, 2020)
Recent research suggests that biochar amendment is a promising approach to mitigate soil contamination via immobilizing heavy metals and organic pollutants. Through intensive literature review, this paper was aimed to better understand the processes, mechanisms, and effectiveness of biochar immobilizing chemical contaminants in soil. The quality characteristics of biochar as a soil amendment varied greatly with the feedstock materials and the pyrolysis conditions. Biochar products from different sources demonstrated remarkably diversified capacities and efficiencies for stabilizing soil contaminants. Soil-incorporated biochar was able to stabilize Cd, Cu, Ni, Pb, and Zn and reduce their bioavailability through enhanced sorption (based on electrostatic attraction, ion exchange, and surface complexation) and chemical precipitation (incurred from soil pH elevation and ash addition of carbonates and phosphates). The stabilization efficacy was largely determined by cation exchange capacity (CEC), pH, and ash content of biochar. Biochar amendment increased the mobility of anionic toxic elements (e.g., CrO42-, AsO3-, and Sb(OH)6-) in soil. Soil-incorporated biochar was also able to adsorb nonpolar organic compounds (through pore-filling, partition, and hydrophobic effect) and polar organic compounds (via H-bonding, electrostatic attraction, specific interaction, and surface precipitation). The adsorption efficiency was controlled by the biochar surface properties specific surface area (SSA), microporosity, and hydrophobicity. Biochar may facilitate mineralization of organic pollutants by enhancing soil microbial activities. The effectiveness of biochar-facilitated soil remediation was case-specific, changing with the biochar source, amendment rate, placement, soil type, and pollutant species. More field studies are needed to evaluate the long-term effectiveness of biochar-facilitated soil remediation under practical circumstances.